2004
DOI: 10.1007/s00402-004-0697-y
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic fracture of the distal femur in osteitis fibrosa cystica simulating metastatic disease

Abstract: A 32-year-old woman sustained a minor sliding accident with moderate to severe pain about the left distal thigh and hip and the right shoulder. Radiographs showed marked osteopenia, multiple osteolytic bone lesions, and a pathologic fracture of the left distal femur. Surgical intervention was conducted for the pathologic fracture, and the pathological findings confirmed the diagnosis of primary hyperparathyroidism with osteitis fibrosa cystica. We report this rare case here because it may be mistaken for neopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 18 publications
1
51
0
Order By: Relevance
“…Elevated levels of serum calcium, alkaline phosphatase, and PTH, and decreased serum phosphate level are diagnostic indicators of PHPT, as in the present case (3,12).…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Elevated levels of serum calcium, alkaline phosphatase, and PTH, and decreased serum phosphate level are diagnostic indicators of PHPT, as in the present case (3,12).…”
Section: Discussionsupporting
confidence: 64%
“…Singhal et al (15) reported that 5%-15% of patients with PHPT have associated bony abnormalities. The skeletal involvement includes diffuse osteoporosis or polyostotic lytic bone lesions, which are manifested clinically by diffuse or focal bone pain, or pathologic fractures involving osteolytic bone lesions (3,4,12). Radiologic examination reveals osteopenia of the entire skeleton and multiple localized lytic lesions with a benign aspect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The histopathology shows diffuse proliferation of the osteoclastic multinucleated giant cells mixed with fibro cellular proliferation and hemorrhagic foci, with release of hemosiderin so appears as reddish-brown mass. 5,6 However, the histopathological diagnosis feature alone cannot confirm the diagnosis because other giant cell lesions such as giant cell granuloma is similar to the lesions therefore, patients with giant cell tumors should be included in investigation for the presence or absence of hyperparathyroidism in order to differentiate these types of granuloma from brown tumors.…”
Section: Discussionmentioning
confidence: 99%